Antifragility and the development of urban water infrastructure. Issue 4 (4th July 2018) - Babovic, Filip; Babovic, Vladan; Mijic, Ana
Abstract: Antifragility is a system property that results in systems becoming increasingly resistant to external shocks by being exposed to them. These systems have the counter-intuitive property of benefiting from uncertain conditions. This paper presents one of the first known applications of antifragility to water infrastructure systems and outlines the development of antifragility at the city scale through the use of local governance, data collection and a bimodal strategy for infrastructure development. The systems architecture presented results in a management paradigm that can deliver reliable water systems in the face of highly uncertain future conditions.